2022
DOI: 10.3390/ijms23116096
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Negatively Regulates RANKL-Induced Osteoclastogenesis of Mouse Bone Marrow Macrophages but Positively Regulates It in the Presence of Lipopolysaccharides

Abstract: In inflammatory bone diseases such as periodontitis, the nucleotide-binding oligomerization domain, leucine-rich repeat, and pyrin domain-containing 3 (NLRP3) inflammasome accelerates bone resorption by promoting proinflammatory cytokine IL-1β production. However, the role of the NLRP3 inflammasome in physiological bone remodeling remains unclear. Here, we investigated its role in osteoclastogenesis in the presence and absence of lipopolysaccharide (LPS), a Gram-negative bacterial component. When bone marrow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“… 51 Pro-inflammatory macrophages can elevate local expression of RANKL, which promotes osteoclast differentiation in the periodontium. 52 , 53 In contrast, anti-inflammatory macrophages are involved in inflammation resolution and tissue regeneration via the secretion of anti-inflammatory mediators. 54 In addition, anti-inflammatory macrophages contribute to the exocytosis of apoptotic osteoblasts and mediate bone formation.…”
Section: Discussionmentioning
confidence: 99%
“… 51 Pro-inflammatory macrophages can elevate local expression of RANKL, which promotes osteoclast differentiation in the periodontium. 52 , 53 In contrast, anti-inflammatory macrophages are involved in inflammation resolution and tissue regeneration via the secretion of anti-inflammatory mediators. 54 In addition, anti-inflammatory macrophages contribute to the exocytosis of apoptotic osteoblasts and mediate bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In inflammatory bone diseases such as periodontitis, the NLRP3 inflammasome promotes bone resorption by inducing the production of the pro-inflammatory cytokine IL-1β. Studies have investigated its role in osteoclastogenesis in the presence and absence of LPS and have found that the NLRP3 inflammasome promotes osteoclastogenesis via IL-1β during infection, but inhibits osteoclastogenesis by inducing pyroptosis of osteoclast precursor cells under physiological conditions (Alam et al, 2022).…”
Section: Osteoclastsmentioning
confidence: 99%
“…Under infectious conditions, inflammasome activation promoted bone loss due to induced osteoclast formation mediated by IL‐1B production, probably to eliminate injured bone or pathogens around bone. Meanwhile, under physiological conditions, the inflammasome seemed to inhibit osteoclast formation via pyroptosis and helped to maintain bone homeostasis 213 . Moreover, activation of the inflammasome stimulates M1 polarization 196 .…”
Section: Implant‐related Factors Altering Bone Metabolismmentioning
confidence: 99%